Effect of pouring temperature on fluidity, porosity, density, and microstructure of Al-Si alloy in gravity die casting - Sudarsono; Amir Arifin; Hidayat; La Ode Ahmad Barata; Aminur; Alain Kusmoko (CV. Literasi Indonesia, 2026)
The growing demand for lightweight aluminium components necessitates improved quality control in casting, particularly for aluminium–silicon (Al–Si) alloys produced via gravity die casting. This study systematically investigates the effect of pouring temperature on the fluidity, porosity, density, and microstructure of an Al–Si alloy using a gravity iron die mold with varying section thicknesses. Casting experiments were conducted at pouring temperatures of 600°C, 650°C, and 700°C to simulate thin-wall casting conditions. Fluidity was evaluated by measuring flow length, while density and porosity were determined using Archimedes’ principle. Microstructural evolution was characterized via optical microscopy. The results demonstrate that increasing the pouring temperature significantly enhances fluidity, enabling the complete filling of progressively thinner sections. However, higher temperatures also lead to increased porosity and reduced density, particularly in thicker sections, due to prolonged solidification times and reduced cooling rates. Microstructural analysis reveals that higher pouring temperatures and larger section thicknesses promote coarser α-Al dendrites, larger β-Si particles, and increased intermetallic phase aggregation; conversely, lower pouring temperatures and thinner sections result in finer, more homogeneous microstructures. These findings highlight the critical trade-off between mold-filling capability and internal casting quality, emphasizing the importance of optimizing pouring temperature in the gravity die casting of Al–Si alloys.